2002
DOI: 10.1002/ecjb.1091
|View full text |Cite
|
Sign up to set email alerts
|

Design of a microwave variable delay line using liquid crystal, and a study of its insertion loss

Abstract: SUMMARYA microwave variable delay line was designed and fabricated using a nematic liquid crystal for the dielectric substrate of the microstrip line, and the phase characteristics and insertion losses of the device were evaluated. The phase shift characteristics were found to be in close agreement with the design value, indicating the ability to implement wide-band variable delay lines over a microwave frequency range. The insertion losses of the fabricated variable delay line were found to be too high for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…A recent detailed study 10 published in 2010, has reported values of the effective loss tangent for conventional nematic LC devices at the millimeter wavelength range (30 GHz). Loss tangent, in static (from 0.01 to 0.06) and dynamic (from 0.04 to 0.001) regimes, were, in the worst case, one order of magnitude greater than that of conventional dielectrics such as teflon 11 and, therefore, were expected to be higher for microwave applications; this constraint has been treated as tolerable low losses.…”
mentioning
confidence: 99%
“…A recent detailed study 10 published in 2010, has reported values of the effective loss tangent for conventional nematic LC devices at the millimeter wavelength range (30 GHz). Loss tangent, in static (from 0.01 to 0.06) and dynamic (from 0.04 to 0.001) regimes, were, in the worst case, one order of magnitude greater than that of conventional dielectrics such as teflon 11 and, therefore, were expected to be higher for microwave applications; this constraint has been treated as tolerable low losses.…”
mentioning
confidence: 99%
“…The most effective way to achieve a small value of τ d is to reduce d. When d is decreased, however, the transmission loss is increased in a delay line with the microstrip line structure, for example [9]. Thus, the following structural measure is much more important than the selection of the liquid crystal material: for high-frequency application, the value of d should not be decreased, but the effective thickness between the two rubbing layers should be minimized so that the orientation force required to return the orientation to the initial state of the liquid crystal is affected.…”
Section: Response Time Measurements and Discussionmentioning
confidence: 98%
“…(15), d must be decreased in order to achieve high speed. On the other hand, this increases the conductor loss in the microstrip line [9]. Consequently, in order to develop a delay line with low loss and small τ d , it is important to design a structure that can effectively reduce d by enhancing the orientation effect without decreasing the actual liquid crystal layer thickness.…”
Section: −4mentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 2(c)-(d), to millimeter-or bulkier microwave devices for tunable -delay line, -phase shifter, -wavelength selector and beam steering devices [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], to name a few. Nematic liquid crystals are uni-axial, characterized by refractive indices n and the n ⊥ , for light polarization parallel and orthogonal to the director axis, respectively.…”
Section: F Figures 2(a)-(b)mentioning
confidence: 99%